The Effect Of Service Quality And Price Discounts Of “The Blessed Friday” Program On Customer Satisfaction (A Case Study At Ditha Facial Salon, Bojonggede) - Kuraesin, Ecin; Sephiana, Della; Sinaga, Hanif Zaidan (INOVATOR, 2025)
This study aims to examine the effect of profitability (return on assets), liquidity, leverage, Maintaining customer loyalty requires excellent service and attractive pricing strategies. This study aims to examine the influence of service quality and price discounts on customer satisfaction at Dithafacial Salon Bojonggede, focusing specifically on the “Jumat Berkah” (Blessed Friday) promotional program. The research employed a quantitative approach, collecting data through questionnaires distributed to 60 respondents. Data analysis was conducted using validity and reliability tests, multiple linear regression, t-tests, and F-tests to assess the effect of each variable. The results indicate that service quality has a significant impact on customer satisfaction. Price discounts also show a positive influence, although not as strong as service quality. Simultaneously, both variables affect customer satisfaction. It can be concluded that the success of promotional programs such as “Jumat Berkah” depends not only on the discounts offered but also heavily on the consistency and professionalism of the services provided. Reliable and high-quality service remains the key factor in encouraging repeat visits and building customer loyalty.